Civil Disobedience and the Politics of Identity - Hill, J. author. aut Link
XX, 201 p.
Keywords: Civil Disobedience and the Politics of Identity is an attempt to provide criteria for when it is both morally necessary and politically expedient to break with civic harmony social cohesion in the name of a higher social justice.